Summary procedure and presumption of innocence: implications in the Ecuadorian judicial system through a SWOT analysis - Guambo Llerena, Miguel Angel; Gavilanes Capelo, Dolores Berthila; Guambo Gavilanes, Gabriela Michel (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
The text addresses the expedited procedure in the Ecuadorian judicial system, focusing on its implications for the presumption of innocence and other fundamental rights of the accused. It emphasizes that, while the expedited procedure streamlines the judicial process and reduces the workload of the courts, it also poses significant risks. These include potential violations of the right against self-incrimination, rushed decisions by the accused due to pressures or lack of resources for a full defense, and public perception of transparency shortcomings in agreements. The importance of the presumption of innocence, enshrined in the Ecuadorian Constitution and international treaties, is discussed to ensure a fair process that respects the rights of all involved. Reforms are suggested to balance judicial system efficiency with the protection of individual rights, highlighting the need for continuous training for judicial operators and rigorous oversight of agreements under the expedited procedure.